2005
DOI: 10.1029/2004jd004661
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric wave response to decelerated stratosphere seen as downward propagation in northern annular mode

Abstract: [1] Baldwin and Dunkerton [1999] found that negative northern annular mode (NAM) anomalies sometimes descend all the way from the stratosphere into the lower troposphere. However, no viable mechanism has been proposed so far to account for the magnitude of the anomalies in the denser troposphere. Further, analysis shows that the character of the anomaly changes across the tropopause. Above the tropopause the NAM pattern is approximately zonal, and its descent represents the descent of decelerated zonal mean w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
(25 reference statements)
1
13
0
Order By: Relevance
“…However, as shown here and in the previous paper (Coughlin and Tung 2005), the EOF pattern also contains a wave 1 structure, which gives rise to a change in the tropospheric NAM index. Such examples may be more easily understood with a classical framework of the vertical propagation of planetary waves and wave mean-flow interaction.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…However, as shown here and in the previous paper (Coughlin and Tung 2005), the EOF pattern also contains a wave 1 structure, which gives rise to a change in the tropospheric NAM index. Such examples may be more easily understood with a classical framework of the vertical propagation of planetary waves and wave mean-flow interaction.…”
Section: Discussionsupporting
confidence: 79%
“…2 in Coughlin and Tung (2005) reveals that prior to the change in the stratospheric NAM index, the NAM index in the troposphere changes due to the wave 1 component. However, during the winter, variability is large both in the stratosphere and troposphere so that it is difficult to see a causal relationship between them.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There had not been enough experimental evidences for such a connection till date. However, some of the recent studies discussing the dynamical changes in the lower atmosphere over the northern high latitude regions not only indicate the presence of a zero wind line but also discuss about significance in context of the propagation of PWs (Baldwin and Dunkerton, 1999;Walterscheid et al, 2000;Coughlin and Tung, 2005;Liu and Roble, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In support with this, Coughlin and Tung (2005) have shown that the quasi-stationary planetary waves in the troposphere are also sensitive to the stratospheric conditions, so they can also respond to downward propagating stratospheric anomalies in zonal-mean zonal windū. Note here that the various mechanisms listed here and before are not exclusive with each other, with the "downward control" effect for instance, and the effect due to the planetary waves reinforcing each other in Song and Robinson (2004).…”
Section: Introductionmentioning
confidence: 71%